Critically evaluating university mission and vision statements - Marc D. Sakellarios; David A. Gann (Institute of Advanced Engineering and Science, 2024)
The purpose of this article is to better understand the nature of mission and vision statements issued by universities and whether these statements reflect the values of the institution’s leaders, faculties, and students. The researchers, being employed as professors in a Japanese science university, sought to analyze their own institution’s mission statement using open, axial, and selective (OAS) coding as an evaluation methodology. The themes that emerged were those of the great man, elite education, and alumni exclusivity. The overarching theme of the mission statement was elite serving the elite. Although presented as a mission statement, the prominence of the theme of a visionary man suggests this document stylistically adheres as much to the characteristics of a vision statement as it does to a mission statement. This paper may assist teachers in deriving meaning from their institution’s mission or vision statements, and critically assessing whether the institution’s mission or vision comports with the beliefs, standards, and educational philosophies evidenced by their institution in practice.